2016
DOI: 10.1016/j.apor.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Scour below a subsea pipeline in time varying flow conditions

Abstract: This paper presents results of an experimental investigation into the time scale of local scour and backfill for a subsea pipeline in changing flow conditions, modelled as two consecutive but different flow conditions and as uniformly increasing flow velocities. Unidirectional current flow, waves and combined waves and current flow are all considered. Based on the results of the experiments, effective time scales of the scour and backfill are quantified and algorithms to predict the scour process in changing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Hence, the present experiments are in line with the conclusion of , that the scour depth following a change in flow conditions will tend to a new equilibrium based solely on the new wave condition. This conclusion is similarly backed by other experimental (Bayraktar et al, 2016;Zhang et al, 2016Zhang et al, , 2017 and numerical (Fuhrman et al, 2014;Bayraktar et al, 2016) research. Fuhrman et al (2014) also found that the equilibrium bed profiles (i.e.…”
Section: Scour Depth Time Series and Profilessupporting
confidence: 80%
See 1 more Smart Citation
“…Hence, the present experiments are in line with the conclusion of , that the scour depth following a change in flow conditions will tend to a new equilibrium based solely on the new wave condition. This conclusion is similarly backed by other experimental (Bayraktar et al, 2016;Zhang et al, 2016Zhang et al, , 2017 and numerical (Fuhrman et al, 2014;Bayraktar et al, 2016) research. Fuhrman et al (2014) also found that the equilibrium bed profiles (i.e.…”
Section: Scour Depth Time Series and Profilessupporting
confidence: 80%
“…Local pipeline scour and/or backfilling processes due to current and/or waves have been commonly studied both experimentally (e.g. Sumer and Fredsøe, 1990;Zhang et al, 2016;Bayraktar et al, 2016) as well as numerically (e.g. Brørs, 1999;Liang and Cheng, 2005;Kazeminezhad et al, 2012;Zanganeh et al, 2012;Fuhrman et al, 2014;Larsen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have focused on the two-dimensional scour under a pipeline, wherein the currents or waves are assumed to propagate towards the pipeline perpendicularly and the properties of the pipeline and the sediment are supposed to be identical along the pipeline [2]. These investigations have focused on the mechanism of the onset of scour [3,4], the equilibrium scour depth [5][6][7], the time scale of tunnel erosion [8][9][10], and field observations and tests [11,12]. Numerical simulation is also widely adopted in researches on the two-dimensional scour hole development process [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The operating speed and precision for installing pipelines and other deep-sea equipment need to constantly improve to adapt to increasing developmental requirements [1,2]. Vessel motion and installation are highly sensitive to environmental changes during pipeline installation [3,4]. It is essential to acquire a better understanding of the marine environment during installation to provide these operations with higher accuracy, which can significantly help with planning pipeline installation.…”
Section: Introductionmentioning
confidence: 99%